Diary of a wimpy kid : the long haul - Kinney, Jeff. (London : Penguen, 2016)
The Heffley family road trip starts off full of promise, then quickly takes several wrong turns--with everything from a fender bender to crazed seagulls--but even the worst road trip can turn into an adventure, and this is one the Heffleys will not soon forget.
Horn Book
Publishers Weekly Annex
Horn Book, October 2015
Publishers Weekly Annex, November 2014
5.4
5-8
Keywords: Automobile travel -- Juvenile fiction; Families -- Juvenile fiction; Vacations -- Juvenile fiction; Automobile travel -- Fiction; Diaries -- Fiction; Family life -- Fiction; Humorous stories; Vacations -- Fiction; Automobile travel -- Fiction; Family life -- Fiction; Vacations -- Fiction; Diary fiction; Humorous fiction